1998
DOI: 10.1055/s-1998-1598
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Transition Metal-Catalyzed Route to Functionalized Dihydropyrans and Tetrahydrooxepines

Abstract: A straightforward route for the synthesis of α,α'-disubstituted dihydropyrans and tetrahydrooxepines has been developed involving Pd-and Ru-catalyzed reactions.2,6-Disubstituted dihydropyrans 1 and 2 (n = 1) occur frequently in nature as a structural unit in a wide range of natural products. 1 In addition, these compounds could serve as useful building blocks for the synthesis of biologically active saturated oxygen heterocycles via functionalization of the double bond. Examples include (poly)cyclic ethers, 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 4 publications
2
36
0
2
Order By: Relevance
“…[25] Uns gelang die Synthese von acyclischen Dien-Vorstufen (30, 33) über eine Palladium(ii)-katalysierte Kupplung eines Alkohols (oder eines Sulfonamids) mit Methoxyallen in guter Ausbeute (Schema 7). [26][27][28][29] Die RCM der gemischten Acetale (30) und Aminale (33) mithilfe des Grubbs-Katalysators der zweiten Generation 7 und die nachfolgende Umsetzung der Zwischenprodukte mit TFA zur Eliminierung von Methanol führte in guten Gesamtausbeuten zu den substituierten Furan-(31) und Pyrrolderivaten (34). Es sollte erwähnt werden, dass Rutjes et al zuvor über die Bildung von N-Tosylpyrrol infolge einer ähnlichen Abbaureaktion eines entsprechenden RCM-Intermediats an Kieselgel berichtet hatten.…”
Section: Rcm Mit Anschließender Eliminierung Einer a C H T U N G T R unclassified
“…[25] Uns gelang die Synthese von acyclischen Dien-Vorstufen (30, 33) über eine Palladium(ii)-katalysierte Kupplung eines Alkohols (oder eines Sulfonamids) mit Methoxyallen in guter Ausbeute (Schema 7). [26][27][28][29] Die RCM der gemischten Acetale (30) und Aminale (33) mithilfe des Grubbs-Katalysators der zweiten Generation 7 und die nachfolgende Umsetzung der Zwischenprodukte mit TFA zur Eliminierung von Methanol führte in guten Gesamtausbeuten zu den substituierten Furan-(31) und Pyrrolderivaten (34). Es sollte erwähnt werden, dass Rutjes et al zuvor über die Bildung von N-Tosylpyrrol infolge einer ähnlichen Abbaureaktion eines entsprechenden RCM-Intermediats an Kieselgel berichtet hatten.…”
Section: Rcm Mit Anschließender Eliminierung Einer a C H T U N G T R unclassified
“…Examples 11c, d, e illustrate that the rapid assembly of substrates for ring closing metathesis reactions is possible using the Pd-catalyzed allylation reaction. Precursors 10c [45] and 10e [46] have been prepared in one step by addition of allyl-or allenylmetal compounds to ethyl glyoxalate. Ester 10d is available in one step from dimethyl malate via a highly diastereoselective enolate allylation, using a method described by Seebach et al [47] The ratio of diastereomers observed for 10d is not altered during the O-allylation.…”
Section: Resultsmentioning
confidence: 99%
“…Optical purities were determined by HPLC using a HP-LC-1050 system equipped with a Daicel Chiralcel OD column. The following compounds were prepared according to procedures described in the literature: 10c, [45] 10d, [47] 10e, [46] 10g, [49] 10h, [56] 10i, [3] 10j, [57] Pd 2 (dba) 3 · CHCl 3 , [58] [Pd(h 3 -C 3 H 5 )Cl] 2 , [59] and [Pd(PPh 3 ) 4 ]. [58] Screening Experiments for Different Pd-Precatalysts…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protecting group manipulation and stereoselective allylation using Spilling's protocol 49 gave the C-glycoside 54. The acidsensitive A-ring, containing a (2S)-3-butene-1,2-diol side- 50 Palladium-catalyzed acetalization of secondary alcohol 54 with 1-phenoxy-1,2-propadiene according to the Rutjes's procedure 51 yielded a mixture of allylic acetals, 55 and 56, in 45 and 32% yields, respectively. After separation, the undesired isomer 56 was epimerized by treatment with palladium catalyst and phenol to produce the desired 55.…”
Section: Preparation Of Anti-ctx3c Antibodies For Bothmentioning
confidence: 99%